Characterization of a broad spectrum bacteriocin produced by Lactobacillus plantarum MXG-68 from Inner Mongolia traditional fermented koumiss - Man, Li-Li; Xiang, Dian-Jun (Folia microbiologica, 2019)
An agar well diffusion assay (AWDA) was used to isolate a high bacteriocin-producing strain with a broad spectrum of antibacterial activity, strain MXG-68, from Inner Mongolia traditional fermented koumiss. Lactobacillus plantarum MXG-68 was identified by morphological, biochemical, and physiological characteristics and 16S rDNA analysis. The production of antibacterial substance followed a growth-interrelated model, starting at the late lag phase of 4 h and arriving at a maximum value in the middle of the stationary phase at 24 h. Antibacterial activity was abolished or decreased in the presence of pepsin, chymotrypsin, trypsin, proteinase, and papain K. The results showed that antibacterial substances produced by L. plantarum MXG-68 were proteinaceous and could thus be classified as the bacteriocin, named plantaricin MXG-68. The molar mass of plantaricin MXG-68 was estimated to be 6.5 kDa, and the amino acid sequence of its N-terminal was determined to be VYGPAGIFNT. The mode of plantaricin MXG-68 action was determined to be bactericidal. Bacteriocin in cell-free supernatant (CFS) at pH 7 was stable at different temperatures (60 °C, 80 °C, 100 °C, 121 °C for 30 min; 4 °C and - 20 °C for 30 days), as well as at pH 2.0-10.0. Antibacterial activity maintained stable after treatment with organic solvents, surfactants, and detergents but increased in response to EDTA. Response surface methodology (RSM) revealed the optimum conditions of bacteriocin production in L. plantarum MXG-68, and the bacteriocin production in medium optimized by RSM was 26.10% higher than that in the basal MRS medium.
Keywords: Čína; kinetika; stabilita proteinů; Molecular Weight; Lactobacillus plantarum; RNA, Ribosomal, 16S; sekvence aminokyselin; Anti-Bacterial Agents; kumys; potravinářská mikrobiologie; molekulová hmotnost; Food Microbiology; Characterization; China; bakteriociny; Protein Stability; Bacteriocins; RNA ribozomální 16S; Screening; Amino Acid Sequence; fylogeneze; Bacteriocin; antibakteriální látky; Kinetics; kultivační média; Response surface methodology; Koumiss; Phylogeny; Staphylococcus; Culture Media